EFEKTIVITAS PENEGAKAN DISIPLIN PEGAWAI NEGERI SIPIL DI LINGKUNGAN BADAN KEPEGAWAIAN DAERAH KABUPATEN SIAK - Iis Desmanella; Zaili RUSLI (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The number of minor disciplinary offenses committed by civil servants in the localgovernment environment. Siak, requires local governments in enforcing discipline inanticipation of such breach. The problem in this study is how the effectiveness of theenforcement of discipline in the civil service environment Siak Regional Employment Boardand the factors that affect the enforcement of discipline. As for the purpose of this researchwas to determine the effectiveness of the enforcement of discipline in the civil serviceenvironment Siak Regional Employment Board and to determine the factors that influencethe effectiveness of the enforcement of discipline.The concept of the theory is that researchers use effectiveness, organization anddiscipline. This study used qualitative research methods to the assessment of descriptive data.In collecting the data, the researcher used interview techniques, observation and study ofliterature. By using key informants as a source of information.The results of this study show that the effectiveness of the discipline of civil servantsin the Regional Employment Board Siak quite effective. Factors that influence theeffectiveness of this discipline is Chairman, remuneration, supervision attached, legalsanctions, mindset and justice.Keywords: Effectiveness, Enforcement Discipline